Linguistic Manipulation in Gendered Political Campaigns: A Pragmatic Analysis of Suggestion in the Discourse of Female Leadership in Indonesia - Priadi, Arum (Fast in Social Sciences, 2025)
This study investigates the practice of linguistic manipulation in political campaigns by female figures in Indonesia, focusing on the use of suggestive strategies in constructing leadership discourse. The research is grounded in the assumption that women in politics face challenges in establishing authority amid gender-biased social expectations. To address these challenges, female political actors tend to rely on persuasive yet indirect language, employing suggestive structures that operate implicitly through context. The study aims to identify the forms and distribution of suggestive strategies and to describe how they function in framing authority, trust, and emotional connection with the public. Employing a qualitative approach supported by corpus analysis using AntConc software version 4.2.0, the study adopts Relevance Theory and Hypnotic Language Pattern as its theoretical framework, providing a conceptual basis for analyzing implicit meanings and the persuasive power of suggestion in political communication. Primary data were drawn from transcripts of speeches, public debates, and social media posts by Indonesian female politicians, while secondary data included online media articles and public documentation. Features such as Word List, Collocates, Concordance, and N-Grams were utilized to identify frequency, collocation patterns, contextual distribution, and suggestive phrase structures. Manual coding was conducted based on ten categories of linguistic suggestion, validated through a Cohen’s Kappa test (κ = 0.86), indicating a very high level of agreement. The findings reveal that presupposition accounted for 29.3% of all suggestive utterances, followed by embedded commands (21.7%), vague language (14.6%), and universal quantifiers (12.1%). Tag questions and double binds contributed 7.9% and 6.4%, respectively, while the remainder was distributed among truisms, implied cause-effect, and comparative deletion. Suggestive utterances were most prevalent in public speech texts (46.5%), followed by social media posts (33.2%) and media quotations (20.3%). Contextual distribution showed that suggestive strategies were intensively employed in the opening and closing segments of campaigns, as well as in parts emphasizing emotional proximity and calls to action.